IMPLEMENTASI KEBIJAKAN PAJAK AIT TANAH DI KOTA TEGAL (KAJIAN PERDA NOMOR 2 TAHUN 2011 TENTANG PAJAK AIR TANAH) - Ovani, M. Izur Rifki; Suwitri, Sri; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Groundwater tax is one type that is managed by the local tax . Tax groundwater previously managed by the provincial government then managed entirely by local governments as a form of decentralization . Implementation of tax policy at Tegal ground water is fully regulated in Regulation No. 2 of 2011 About Tax Groundwater . Authorized agency in terms of tax collection and management of ground water is Revenue Service, Management, Finance and Public Asset ( DPPKAD). Local regulations governing the issuance of tax policy groundwater is one of the efforts to preserve and control of groundwater use , so that it can be used on an ongoing basis and the tax function as a source of income to finance a useful area for regional development. This study aims to explain how tax policy implementation groundwater management in Tegal and identify aspects that support and hinder the implementation of tax policy groundwater managed by DPPKAD Tegal and is expected to become an input for implementing this policy.Supporting and inhibiting aspects identified aspects of the phenomenon of financial resources, economic conditions, social and political society, communication, and characteristics of the implementing agency. This is a descriptive qualitative study, using snowballing sampling technique. This study shows that the implementation of the groundwater tax already well proven with the successful achievement of the groundwater tax revenue , but there are some obstacles in its implementation. Many inhibiting factors that affect the implementation of groundwater tax collection, there are limited budget, yet comprehensive level of consciousness by taxpayer, and the lack of participation of the taxpayer and lack of socialization because DPPKAD has never held a formal socialization.